1929
DOI: 10.1084/jem.50.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Inflammation

Abstract: Trypan blue injected into normal subcutaneous tissue passes rapidly to the regional lymphatic node and is found in lymph drawn from its efferent lymphatic. When the dye is injected into the normal peritoneal cavity it rapidly appears in the lymph of the retrosternal lymphatics and stains deeply the retrosternal lymphatic nodes. Trypan blue injected into the site of inflammation in the subcutaneous tissue or in the peritoneal cavity is fixed in the inflamed area and fails to reach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1930
1930
1967
1967

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…The localization of dye is a phenomenon of skin inflammation and is nonspecific, with no immunologie basis. 4 Microscopic examination of biopsies, taken 24 hr. after intradermal injections of serum, in cases of inflammatory reac¬ tions, shows a rather pronounced polymorphonuclear-cell infiltration.…”
Section: Commentmentioning
confidence: 99%
“…The localization of dye is a phenomenon of skin inflammation and is nonspecific, with no immunologie basis. 4 Microscopic examination of biopsies, taken 24 hr. after intradermal injections of serum, in cases of inflammatory reac¬ tions, shows a rather pronounced polymorphonuclear-cell infiltration.…”
Section: Commentmentioning
confidence: 99%
“…The dye was used in concentrations of 0.25 per cent to 0.5 per cent, and from 6 to 40 cc. of dye were necessary to administer the proper amount of radioactivity, depending on what period of time had elapsed after the standardization measurements 8 Methods of production of free bromine from the cyclotron targets, the synthesis of the dye, its purification and properties are to be described in a subsequent paper (20).…”
Section: Dosage and Counting Techniquementioning
confidence: 99%
“…This does not necessarily mean that the fall in concentration of dye within the capillaries is a measure of the amount of dye that passes through their walls, for it is conceivable that there may be other factors that change the concentration of dye within the capillaries in an inflamed area. However, in view of previous studies (10) in which it has been shown that trypan blue injected intravenously rapidly passes into an inflamed area, it is believed that the increased rate of fall of concentration is a measure of increased passage of the dye through the capillary wall.…”
Section: Concentration Of Dye (Y)mentioning
confidence: 99%
“…Kusnetzowsky (9) also observed that the local application to the skin of an irritant such as heat or mustard oil causes an accumulation of trypan blue in the inflamed area when the dye has previously been injected into the blood stream. It has recently been demonstrated by one of us (10) that try"pan blue injected into the circulating blood enters the site of inflammation rapidly and is fixed there, so that the tissues are deeply stained. Furthermore trypan blue injected directly into the site of inflammation in the subcutaneous tissue or in the peritoneal cavity is fixed in the inflamed area and fails to reach the regional lymphatic nodes.…”
mentioning
confidence: 99%